Parts selection and management - Pecht, Michael G. (John Wiley, 2004)
Increase profitability and reduce risk through effective parts selection and management Corporations recognize that technology can be the key to fueling product design and development. But just as crucial-if not more-to a company's success are the decisions about when, what, and how a technology will be used. Few companies have failed because the right technology was not available; many have failed when a technology was not effectively selected and managed. Parts Selection and Management is a guide to increasing company profitability and reducing the time-to-profit through the efficient management of the process of parts selection and management. Taking an "eyes-on, hands-off" approach to parts selection, this guidebook addresses risk-assessment, decision-making steps, and subsequent management activities. The book covers everything from methodologies for parts selection and management, product requirements and specifications, and manufacturer assessment procedures to ways to track part changes through the supply chain, reliability assessment, and environmental, legislative, and legal issues. Written by a seasoned professional, teacher, and author in the field, the book enables companies to: Employ effective risk assessment and mitigation techniques Make an informed company-wide decision about parts selection and management Choose parts to fit the functionality of the product and other constraints Maximize system supportability by preparing for parts obsolescence Improve supply-chain interactions and communications with customers and regulatory agencies to minimize time-to-profit Shedding light on a neglected but essential aspect of product development, Parts Selection and Management will give your organization the tools you need to avoid the risks associated with product use while promoting flexibility, innovation, and creativity in your product development.